2015
DOI: 10.2147/dddt.s72844
|View full text |Cite
|
Sign up to set email alerts
|

Vipegitide: a folded peptidomimetic partial antagonist of α2β1 integrin with antiplatelet aggregation activity

Abstract: Linear peptides containing the sequence WKTSRTSHY were used as lead compounds to synthesize a novel peptidomimetic antagonist of α2β1 integrin, with platelet aggregation-inhibiting activity, named Vipegitide. Vipegitide is a 13-amino acid, folded peptidomimetic molecule, containing two α-aminoisobutyric acid residues at positions 6 and 8 and not stable in human serum. Substitution of glycine and tryptophan residues at positions 1 and 2, respectively, with a unit of two polyethylene glycol (PEG) molecules yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…As reported, integrin α2β1 is a collagen receptor which can bind to type I, II, III, IV, and XI collagens [33]. Although little is known concerning the integrin α2β1-mediated cell contacting, a previous study revealed that the inhibition of the binding between integrin α2β1 and collagen suppressed platelet aggregation [34], suggesting collagen may mediate the binding between integrins. Plus, collagens are the essential component of ECM and provide both integrity and biological cues for cells [35].…”
Section: Discussionmentioning
confidence: 99%
“…As reported, integrin α2β1 is a collagen receptor which can bind to type I, II, III, IV, and XI collagens [33]. Although little is known concerning the integrin α2β1-mediated cell contacting, a previous study revealed that the inhibition of the binding between integrin α2β1 and collagen suppressed platelet aggregation [34], suggesting collagen may mediate the binding between integrins. Plus, collagens are the essential component of ECM and provide both integrity and biological cues for cells [35].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the first anti- aggregation agent, the chimeric monoclonal c7E3Fab (Abciximab, Reopro) a mAb raised against αIIbβ3 [ 19 ], tirofiban and eptifibatide are small-mass αIIbβ3 antagonists derived from snake venom disintegrins. Vipegitide, a folded KTS-containing peptidomimetic molecule, inhibited the adhesion of α1/α2 integrin toward collagen, and ADP and collagen-I induced platelet aggregation in PRP and whole human blood [ 20 ], providing strategy for developing α2β1 antagonists as antiplatelet agents.…”
Section: Reviewmentioning
confidence: 99%
“…Defect or dysfunction of integrins, in particular of α2β1 integrin, a prominent collagen binding receptor of many cell types [ 3 ] and the only collagen binding integrin on platelets [ 4 ], may affect vascular development and angiogenesis [ 5 ], epithelial cell differentiation [ 6 ], wound repair and fibrosis [ 7 ], inflammation [ 8 , 9 ], and cancer and cancer therapy [ 10 ], as well as collagen-induced platelet activation, hemostasis, and thrombosis [ 4 , 11 ]. Therefore, α2β1 integrin has become a prominent target in drug research [ 12 14 ].…”
Section: Introductionmentioning
confidence: 99%